(untitled) (Global Journal of Science Frontier Research, 2020)
Considering the nutritional values of Mentha viridis. L and Aloe vera plants, these plants can be utilized for the production of alternative cultivation media. The cost of artificial culture media is very high, and some components may be unavailable. Use of the plant-based culture media would drastically reduce the expense of the synthetic media. Fifteen bacterial isolates were isolated from Aloe vera rhizosphere, nine bacterial and nine actinomycetes isolates were isolated from Mentha viridis rhizosphere both cultivated in Sirs EL-Layan, El-Menoufia governorate, Egypt. In-vitro screening was done for the production of indole acetic acid (IAA) and phosphorus solubilization. Results revealed that bacterial isolate No. MB4 produced a high amount of IAA(36.51 µg/ml) on the Mentha-based culture medium, No. A6 showed maximum IAA production (16.25µg/ml) on the Aloe vera-based culture medium and isolate No. MA6 was efficient in phosphorus solubilization (867.85µg/ml) that was isolated from the Mentha viridis. L rhizosphere.16s rRNA analysis of these isolates revealed they are (Pseudomonas monteilii strain CIP 104883, Streptomyces rochei strain DW3 and Kosakonia radicincitans strain DSM 16656 respectively.